Rigid pile response to cyclic lateral loading: laboratory tests - Abadie, C; Byrne, B; Houlsby, G (Thomas Telford, 2019)
This paper presents experimental work aimed at improving understanding of the behaviour of rigid monopiles, in cohesionless soils, subjected to lateral cyclic loading. It involves 1g laboratory model tests, scaled to represent monopile foundations for offshore wind turbines. The test programme is designed to identify the key mechanisms governing pile response, and is divided into four main parts: (a) investigation of loading rate effects; (b) hysteretic behaviour during unloading and reloading; (c) pile response due to long-term single-amplitude cyclic loading; and (d) multi-amplitude cyclic loads. The results show that the pile response conforms closely to the extended Masing rules, with additional permanent deformation accumulated during non-symmetric cyclic loads. This ratcheting behaviour is characterised by two features: first, the ratcheting rate decreases with cycle number and depends on the cyclic load magnitude, and second, the shape of the hysteresis loop tightens progressively, involving increased secant stiffness and decreased loop area. Test results involving multi-amplitude load scenarios demonstrate that the response of the pile to complex load scenarios can be analysed and understood using the conclusions from single-amplitude cyclic loading. Such test results should be sufficient for deriving the principles of new modelling approaches.